Histopathological and risk factor analyses of oral potentially malignant disorders and oral cancer in a proactive screening in northeastern Thailand - Boworn Klongnoi; Vanvisa Sresumatchai; Harin Clypuing; Angkana Wisutthajaree; Jintana Pankam; Natchalee Srimaneekarn; Binit Shrestha; Siribang-on Piboonniyom Khovidhunkit (BMC, 2022)
Abstract Background Lip and oral cavity cancer has been reported as the 10th most common cancer in Thailand. Recently, a screening program for oral potentially malignant disorders (OPMDs) and oral cancer was conducted in the northeastern Thailand which took into consideration a total of 371,911 people who resided in the provinces of Buriram, Chaiyaphum, Nakhon Ratchasima, and Surin. Methods A total of 330,914 subjects were consecutively screened for risk factors of oral cancer by village health volunteers (VHVs) using a questionnaire (S1). Then, 186,710 subjects with one or more risk factors for oral cancer were referred for oral screening by dental auxiliaries or dentists at sub-district level hospitals (S2) where 86,941 subjects were subsequently screened. Afterwards, 1576 subjects with suspicious oral lesions for OPMDs or oral cancer attended local hospitals for further investigation and treatment. Oral medicine specialists, oral surgeons, and local dentists at the district level hospitals performed biopsies and the samples were sent for histopathological analysis. The objectives of the study were to report the histopathology findings from the biopsies obtained from these subjects and the associated risk factors. Results Out of 427 subjects who received biopsies, complete diagnostic results were obtained from 409 patients (462 specimens). The 5 most common histopathological results from these specimens were mild epithelial dysplasia (27.3%), fibroepithelial hyperplasia (14.5%), oral lichen planus/oral lichenoid reactions (11.5%), moderate epithelial dysplasia (8%), and acanthosis with or without hyperkeratosis (5%). Oral squamous cell carcinoma was detected in 14 subjects and 11 other forms of oral cancer were revealed. Among the analyzed risk factors, habitual betel quid chewing was established as a statistically significant risk factor associated with OPMDs and oral cancer. Conclusion The most frequently observed histopathological results of clinically suspected oral cancer and OPMDs included mild epithelial dysplasia, fibroepithelial hyperplasia, oral lichen planus/oral lichenoid reactions, moderate epithelial dysplasia, and acanthosis with or without hyperkeratosis. Betel quid chewing habit was found to be associated with OPMDs and oral cancer.